The causal approach proof for the equivalence of SDKP4 and SQED4 at tree-level - Beltrán, J.; Pimentel, B. M. [UNESP]; Soto, D. E. (World Scientific Publishing, 2020)
The description of the electromagnetic interaction of charged spinless particles is usually formulated by the Scalar Quantum Electrodynamics. However, there is an alternative formulation given by the Duffin-Kemmer-Petiau theory: the Scalar DKP gauge theory. The proof of the equivalence between these two formulations has been discussed in many researches, but there is not yet a conclusive proof. In this paper, we initiate a complete proof in the framework of the Causal Perturbation theory, showing that both scalar formulations provide the same results for the differential cross-section at tree level.
Keywords: causal perturbation theory; DKP; DKP equivalence; SQED; wave packets scattering